Chiledfree Dalam Perspektif Keluarga dan Maqasyid Hukum Perkawinan - Sapri Ali; Syahrial Achmad (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
The term childfree is not something new. The term childfree first appeared in the Merriam-Webster English dictionary before 1901. The childfree phenomenon itself has existed since the 1500s in several countries such as France, England and the Netherlands. The characteristics of a population that works hard, is independent and does not want to be bothered by the presence of children is a strong reason for someone to decide to live without children or be childfree. Islamic law considers that childfree is a decision that is very contrary to one of the goals of marriage that has been established by Allah SWT. In preparing this article, the literature review method was used as the initial approach. A literature review is a holistic, structured, and systematic analysis of literature that includes the process of collecting, selecting, evaluating, and synthesizing information from legal sources. The main focus of the literature review is to provide an in-depth understanding of childfree and the purpose of marriage and maqasyid marriage law.